2012
DOI: 10.1007/s13524-012-0169-x
|View full text |Cite
|
Sign up to set email alerts
|

Nontraditional Families and Childhood Progress Through School: A Comment on Rosenfeld

Abstract: We reexamine Rosenfeld's (2010) study on the association between child outcomes and same-sex family structure. Using the same data set, we replicate and generalize Rosenfeld's findings and show that the implications of his study are different when using either alternative comparison groups or alternative sample restrictions. Compared with traditional married households, we find that children being raised by same-sex couples are 35 % less likely to make normal progress through school; this difference is statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 4 publications
0
43
0
2
Order By: Relevance
“…For empirical evidence challenging this hypothesis, see Aughinbaugh et al (2005). 8 For a comparable debate regarding the import of distinguishing between family structure and family transitions, see the exchange between Allen et al (2013) and Rosenfeld (2013 A second, and larger, group of scholars finds minimal evidence of negative effects of samesex parenting on children. Recent amicus curiae briefs to the US Supreme Court filed by the American Sociological Association (2013,2015) summarize this research on children's academic performance and cognitive development (Potter 2012, Rosenfeld 2010, social development and mental health (Fedewa & Clark 2009, Lamb 2012, Tasker 2005, Wainright & Patterson 2008, and incidence of risky or problematic behaviors (Gartrell et al 2012, Patterson & Wainright 2012, Wainright & Patterson 2006.…”
Section: Same-sex Familiesmentioning
confidence: 99%
“…For empirical evidence challenging this hypothesis, see Aughinbaugh et al (2005). 8 For a comparable debate regarding the import of distinguishing between family structure and family transitions, see the exchange between Allen et al (2013) and Rosenfeld (2013 A second, and larger, group of scholars finds minimal evidence of negative effects of samesex parenting on children. Recent amicus curiae briefs to the US Supreme Court filed by the American Sociological Association (2013,2015) summarize this research on children's academic performance and cognitive development (Potter 2012, Rosenfeld 2010, social development and mental health (Fedewa & Clark 2009, Lamb 2012, Tasker 2005, Wainright & Patterson 2008, and incidence of risky or problematic behaviors (Gartrell et al 2012, Patterson & Wainright 2012, Wainright & Patterson 2006.…”
Section: Same-sex Familiesmentioning
confidence: 99%
“…However, Allen et al (2013) and Allen (2013) questioned Rosenfeld's results. Allen et al (2013) reevaluated Rosenfeld (2010) by using the same U.S. data set but other comparison groups and other sample restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…However, Allen et al (2013) and Allen (2013) questioned Rosenfeld's results. Allen et al (2013) reevaluated Rosenfeld (2010) by using the same U.S. data set but other comparison groups and other sample restrictions. They found that children raised by same-sex couples were significantly less likely than children raised by married couples to make normal progress through school.…”
Section: Introductionmentioning
confidence: 99%
“…Studije prvog vala istraživanja (Wainright, Russell i Patterson, 2004;Wainright i Patterson, 2006, 2008Fedewa i Clark, 2009), kao i studije drugog vala koje nisu našle statistički značajne razlike u ishodima djece (Potter, 2012;Cheng i Powell, 2015;Bos i dr., 2016;Potter i Potter, 2016;Bos, Kuyper i Gartrell, 2017), s iznimkom Rosenfeldova istraživanja (2010), koristile su uzorke s manje od 200 djece istospolnih partnera. S druge strane, studije drugog vala koje su pronašle statistički značajne razlike u štetnim ishodima (Regnerus, 2012a;Allen, 2013;Allen, Pakaluk i Price, 2013;Sullins, 2015aSullins, , 2015b uključivale su više od 500 djece kategorizirane kao djecu iz obitelji istospolnih roditelja.…”
Section: Raspravaunclassified